Learning Socio-Cultural Diversity of Society Containing Tolerance Character Values Through Digital Comic Media - Susanti, Kadek Ayu Citra; Wibawa, I Made Citra (MIMBAR PGSD Undiksha, 2022)
The low use of learning media affects students' motivation to participate in learning. The purpose of this study is to develop a digital comic media containing the value of tolerance characters on the subject of Civics on the topic of community socio-cultural diversity that has been tested for feasibility. This research includes development research. The model used is based on the ADDIE model. However, this research is only in the development stage. The subjects involved were two material experts, two media experts, two practitioners, and ten students. The method used is a questionnaire sheet. The type of data analysis used is descriptive qualitative, and quantitative analysis. The development of digital comics was valid with an average score of 3.93 by material experts with very good qualifications, media experts with 3.75 with very good qualifications, a practitioner with 3.61 with very good qualifications, and student responses with 3.44 with very good qualifications. It means that the digital comic media containing the value of the character of tolerance on the subject of Civics on the topic of socio-cultural diversity for fifth-grade elementary school students is valid and can be used as a learning resource.